PENGARUH FLASH SALE DAN LIVE STREAMING TERHADAP PEMBELIAN IMPULSIF DI MARKETPLACE TIKTOK - Fauziah Amri, Dini; Pauzy, Depy Muhamad; Nadia Ikhwan, Diva; Nurhayati, Astri; Rosiyana, Silva (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2026)
This study aims to analyze the influence of flash sales and live streaming on impulsive buying behavior among TikTok Shop users of Wardah products in Tasikmalaya City. The research employed a quantitative method with a survey approach involving 50 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS 26. The findings indicate that both flash sales and live streaming have a positive and significant effect on impulsive buying, both partially and simultaneously. Flash sales create time pressure and a fear of missing out (FOMO), while live streaming enhances emotional engagement and consumer trust through direct interaction. The R² value of 0.665 shows that these variables explain 66.5% of the variation in impulsive buying behavior. The results confirm that combining interactive promo